Digital teaching resources for teaching Chemistry during the Covid-19 pandemic (Research, Society and Development, 2021)
Chemistry is a science that has its own language, microscopic and generally abstract, which makes it difficult for most students to learn. During remote education, due to the pandemic caused by the new coronavirus, the teaching and learning process becomes even more challenging. Thus, teachers needed to reinvent themselves and adopt new methodologies to meet the demands of this new teaching modality. The use of didactic models in teaching has been reported in the literature as an effective strategy for learning. Therefore, the objective of this work is to evaluate the performance of audiovisual teaching materials (videos), as an intervention for teaching the electronic configuration of the elements. The methodology was qualitative, using a questionnaire applied to 134 1st year high school students at the Federal Institute of Mato Grosso, São Vicente campus, as a validation tool for the efficiency of didactic models. The percentages of responses indicated that the teaching method used is an effective strategy for understanding the content of electronic configuration.